Therapeutic potential of naringin in improving the survival rate of skin flap: A review - Wang, Yincang; Li, Xiaodong; Lv, Hang; Sun, Lin; Liu, Bo; Zhang, Xiaofeng; Xu, Xilin (Frontiers in Pharmacology, 2023)
Naringin is the main component of Drynaria. Modern pharmacological studies have shown that naringin has a wide range of pharmacological activities, including antioxidant, anti-inflammatory, anti-apoptotic, anti-ulcer, and anti-osteoporosis effects. Its therapeutic effects have been observed in various clinical models, such as atherosclerosis, cardiovascular diseases, diabetes, neurodegenerative diseases, and rheumatic diseases. This review investigates the pharmacological effects of naringin and the associated mechanisms in improving flap survival. This review will also provide a reference for future rational application of naringin, especially in research to improve flap survival.